THE INFLUENCE OF STUDENTS’ EDUCATIONAL BACKGROUND AND MOTIVATION IN TAKING RELIGIOUS DEPARTMENT ON THEIR ISLAMIC EDUCATION LEARNING ACHIEVEMENTS - Nurul Qomariyah; Endah Tri Wisudaningsih (UNZAH Genggong, 2021)
This study aims to: (1) determine the effect of the educational background of students majoring in religion on the learning achievement of Islamic religious education students of class XI Religion MAN 2 Kota Probolinggo, (2) determine the effect of student motivation in taking religious education. The Department of Islamic Religious Education in class XI Religion MAN 2 Probolinggo City, (3) knows how the influence of educational background and student motivation in taking the Department of Religion on the learning achievement of Islamic Religious Education students of class XI Religion MAN 2 Kota Probolinggo This research uses a descriptive quantitative approach. The population is students of the Department of Religion, MAN 2, Probolinggo City. The method used was purposive sampling. The research sample was 31 students of class XI Religion. Data collection was carried out using questionnaires, interviews, and documentation. To determine the effect of background and motivation to take a major in religion on learning achievement of Islamic Religious Education in class XI of Religion MAN 2 in Probolinggo City, researchers used multiple linear regression analysis. The t test and f test were analyzed using SPSS 21 for Windows software. The results showed that: (1) The educational background of the students had no effect on the learning achievement of Islamic Religious Education in class XI of Religion MAN 2 in Probolinggo City. This is indicated by t arithmetic <t table = 1.873 <2.048 and a significance level of 0.072> 0.05, (2) Student motivation in joining the department has an effect on the learning achievement of Islamic Religious Education. This is indicated by t count> t table = 2.546> 2.048 and a significance level of 0.017 <0.05, (3). Both of these variables simultaneously affect their Islamic education learning achievement. This is indicated by f count> f table = 4.918> 3.33 and a significance level of 0.015 <0.05. Furthermore, the results showed that the influence of the independent variables, student background and motivation to take the department of religion, on the dependent variable, learning achievement in Islamic education, showed a coefficient of determination (R2) of 0.260 or 26.0%. Keywords: Educational Background, Motivation in Taking Religious Department, Islamic Education Learning Achievement.